The association between surgery type and heart-specific mortality in male breast cancer: Heart-specific mortality in male breast cancer - Sanlı, Ahmet Necati (Journal of Surgery and Medicine, 2025)
Background/Aim: Male breast cancer, while less prevalent than female breast cancer, remains a significant health concern for men. Heart-specific mortality presents a significant worry for male breast cancer patients, as treatment and underlying comorbidities may increase their risk for cardiovascular complications. The purpose of this study was to investigate the associations between the type of surgery and heart-specific mortality in male breast cancer patients. Methods: Data were extracted from the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) 17 tumor registry database. The study encompassed a total of 86 male breast cancer patients who succumbed to heart disease. Patients with missing data on key variables were excluded. We divided the patients into two groups based on the type of surgery they received: breast-conserving surgery (BCS) and mastectomy. Results: The mean age of the BCS group was 78.9 years, while the mean age of the Mastectomy group was 74.7 years. The tumor was most commonly located in the center on both sides. There was no statistically significant difference in the ethnic composition of the groups. All patients in both groups were estrogen receptor (ER) positive. Grade 1 tumors were more prevalent in the BCS group, and Grade 3 tumors were more prevalent in the Mastectomy group. The survival rates did not significantly differ between the two types of surgeries. Conclusion: This study suggests that the type of surgery (BCS or mastectomy) does not significantly affect heart-specific mortality in male breast cancer patients. For a deeper understanding of any additional factors impacting heart-related outcomes in this cohort, further research is required.